2012
DOI: 10.1007/s00359-011-0708-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of bilateral information to determine the walking direction during orientation to a pheromone source in the silkmoth Bombyx mori

Abstract: Odor source localization is an important animal behavior. Male moths locate mates by tracking sex pheromone emitted by conspecific females. During this type of behavior, males exhibit a combination of upwind surge and zigzagging flight. Similarly, the male walking moth Bombyx mori responds to transient pheromone exposure with a surge in movement, followed by sustained zigzagging walking. The initial surge direction is known to be influenced by the pheromone input pattern. Here, we identified the sensory input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 66 publications
1
66
0
Order By: Relevance
“…turning towards the direction of higher pheromone concentration (Takasaki et al, 2012). The optomotor response observed in our experiments is also involved in directional control during surge; therefore, it was convincing that there was an interaction between visual and surge-related olfactory pathways.…”
Section: Research Articlesupporting
confidence: 74%
See 1 more Smart Citation
“…turning towards the direction of higher pheromone concentration (Takasaki et al, 2012). The optomotor response observed in our experiments is also involved in directional control during surge; therefore, it was convincing that there was an interaction between visual and surge-related olfactory pathways.…”
Section: Research Articlesupporting
confidence: 74%
“…1A). The surge is elicited shortly after pheromone detection, during which the moth turns towards the direction of the higher pheromone concentration perceived by the left and right antennae (Takasaki et al, 2012). If the moth loses the pheromone cue, it initiates zigzag walking or consecutive turning from side to side.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural and neurophysiological evidence indicates that the surge is a reflex, while zigzagging and looping are pre-programmed behaviours (we therefore do not discriminate looping from zigzagging) (Olberg, 1983;Kanzaki and Mishima, 1996;Mishima and Kanzaki, 1999;Wada and Kanzaki, 2005;Kanzaki, 2007). Recent behavioural studies reported that the surge direction is modulated by the bilateral olfactory input and optic flow, and is less affected by the wind direction (Takasaki et al, 2012;Pansopha et al, 2014), suggesting that while the silkmoth decides the surge direction through osmotropotaxis, the course control is stabilized by the optomotor response (compensatory movements in response to optic flow). However, silkmoths do not show the optomotor response during the zigzagging phase , suggesting that zigzagging is simply controlled by internal mechanisms.…”
Section: Introductionmentioning
confidence: 84%
“…The wind speed in the canopy was 0.5 m s −1 , which is comparable to the air speed generated by wing fanning in untethered male silkmoths (0.3-0.4 m s −1 ; Loudon and Koehl, 2000) and was not affected by the heading of the robot in the wind tunnel. The surge direction of silkmoths is less affected by wind direction (Takasaki et al, 2012); therefore, the constant air flow in the canopy would not greatly modulate the surge direction.…”
Section: Insect-controlled Robotmentioning
confidence: 99%
See 1 more Smart Citation